Nursing diagnosis: past, present, future - Marjorie Gordon (Universidad de Alicante, 2015)
In this paper I would like to discuss the Past, Present, and Future of the nursing diagnosis, as a category and as a process. There were a series of events that set the stage for the development of nursing diagnoses and a focus on nurses clinical reasoning skills.